Vegetables unleashed : a cookbook - Andrés, José, 1969-; Goulding, Matt (ECCO, 2019)
Andrés is famous for his unstoppable energy<U+2014>and for his belief that vegetables are far sexier than meat can ever be. Showing us how to creatively transpose the flavors of a global pantry onto the produce aisle, Vegetables Unleashed showcases Andrés<U+2019>s wide-ranging vision and borderless cooking style. With recipes highlighting everything from the simple wonders of a humble lentil stew to the endless variations on the classic Spanish gazpacho to the curious genius of potatoes baked in fresh compost, Vegetables Unleashed gives us the recipes, tricks, and tips behind the dishes that have made Andrés one of America<U+2019>s most important chefs and that promise to completely change our relationship with the diverse citizens of the vegetable kingdom. Filled with a guerilla spirit and brought to life by Andrés<U+2019>s globe-trotting culinary adventures, Vegetables Unleashed will show the home cook how to approach cooking vegetables in an entirely fresh and surprising way <U+2013> and that the world can be changed through the power of plants.